2010
DOI: 10.1007/s11269-010-9581-4
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Hierarchy Model for Assessing Global Water Productivity of Irrigation Networks in Iran

Abstract: Water management decisions in irrigation networks are often characterized by complexity, irreversibility and uncertainty. In the present study, an analytical hierarchy model is developed for assessing the Global Water Productivity (GWP) status of irrigation networks. For this purpose 14 criteria, affecting water productivity, and 14 major modern irrigation networks of Iran are analyzed. Dez and Saveh irrigation networks, with the relative weights of 0.112 and 0.045, show the highest and lowest GWP, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…The Analytic Hierarchy Process (AHP) is an effective approach developed by [7] that can be used to solve complex problems and enable effective decision making. Many researches had been applied in several fields, for example, in engineering [8], industry [9], economics [10], environmental management, and water management [11][12][13][14][15][16].…”
Section: Fig 1 Pranburi Watershedmentioning
confidence: 99%
See 1 more Smart Citation
“…The Analytic Hierarchy Process (AHP) is an effective approach developed by [7] that can be used to solve complex problems and enable effective decision making. Many researches had been applied in several fields, for example, in engineering [8], industry [9], economics [10], environmental management, and water management [11][12][13][14][15][16].…”
Section: Fig 1 Pranburi Watershedmentioning
confidence: 99%
“…The findings of [13] showed that the Analytic Hierarchy Model for decision making in the planning the Global Water Productivity (GWP) of irrigation networks in Iran. It can be used to aggregate preferences for obtaining a group decision to improve the choice problems by considering effectively the relevant criteria in the decision making process.…”
Section: Fig 1 Pranburi Watershedmentioning
confidence: 99%
“…The mining allowance of groundwater resource factor (=1 when no mining is allowed) can be considered as the ratio of the groundwater allocation to the irrigation area to the annual recharge of groundwater resources. This definition has been already used by Khare et al (2006), Montazar & Zadbagher (2010), and Montazar (2011). The irrigation water, from Madian River and 396 wells, has a good quality (pH = 7.2-7.7; electrical conductivity-EC = 0.5-3.1 dS m -1 ; sodium adsorption ratio-SAR = 1.2-1.9).…”
Section: Study Areamentioning
confidence: 99%
“…AHP is an effective way to deal with complicated problems that cannot be analyzed by quantitative method completely. The approach has been developed and applied to agricultural and water management numerous areas (Montazar & Behbahani, 2007;Okada et al, 2008a,b;Srdjevic & Medeiros, 2008;Zahang, 2009;Montazar & Zadbagher, 2010). It is directly related to productivity of irrigation systems and greatly contributes to improved soil and water utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Montazar and Zadbagher [9] used AHP in measuring the global water production status in an irrigation network. There are 14 major irrigation networks with 14 attributes to be examined using AHP.…”
Section: Introductionmentioning
confidence: 99%